Acute kidney injury in infants with hypothermia‐treated hypoxic‐ischaemic encephalopathy: An observational population‐based study. (30th August 2021) - Robertsson Grossmann, Katarina; Bárány, Peter; Blennow, Mats; Chromek, Milan
Abstract: Aim: To describe incidence and outcome of acute kidney injury (AKI) in infants with hypothermia‐treated hypoxic‐ischaemic encephalopathy (HIE). Methods: This observational population‐based study included all term and near‐term infants with hypothermia‐treated HIE born between 2007 and 2009 in greater Stockholm. The KDIGO definition modified for neonatal patients was used to identify infants with AKI. We analysed association between AKI and neonatal morbidity/mortality. Furthermore, we calculated estimated glomerular filtration rate (eGFR) at the age of 10–12 years. Results: Out of 83, 939 live births in the Stockholm region, 66 infants underwent hypothermia treatment due to HIE. Out of 65 included infants, 45% suffered AKI. Degree of AKI correlated with HIE severity. One infant needed kidney replacement therapy; others were treated conservatively. AKI was associated with increased mortality and need for blood products ( p  < 0.05). eGFR at age 10–12 years was available for 72% of survivors. Nine children (21%) had subnormal eGFR, with no difference between those with and without a history of neonatal AKI. Conclusion: Despite therapeutic hypothermia, AKI remains a common complication in infants with HIE and is associated with increased neonatal mortality. Twenty‐one per cent of children had subnormal eGFR at 10–12 years, highlighting the need for long‐term follow‐up of renal function.